A simple method for quantifying jump loads in volleyball athletes - Charlton, P. C.; Kenneally-Dabrowski, C.; Sheppard, J.; Spratford, W. (Journal of Science and Medicine in Sport, 2017)
Objectives: Evaluate the validity of a commercially available wearable device, the Vert, for measuring vertical displacement and jump count in volleyball athletes. Propose a potential method of quantifying external load during training and match play within this population. Design: Validation study. Methods: The ability of the Vert device to measure vertical displacement in male, junior elite volleyball athletes was assessed against reference standard laboratory motion analysis. The ability of the Vert device to count jumps during training and match-play was assessed via comparison with retrospective video analysis to determine precision and recall. A method of quantifying external load, known as the load index (LdIx) algorithm was proposed using the product of the jump count and average kinetic energy. Results: Correlation between two separate Vert devices and three-dimensional trajectory data were good to excellent for all jump types performed (r = 0.83-0.97), with a mean bias of between 3.57-4.28 cm. When matched against jumps identified through video analysis, the Vert demonstrated excellent precision (0.995-1.000) evidenced by a low number of false positives. The number of false negatives identified with the Vert was higher resulting in lower recall values (0.814-0.930). Conclusions: The Vert is a commercially available tool that has potential for measuring vertical displacement and jump count in elite junior volleyball athletes without the need for time-consuming analysis and bespoke software. Subsequently, allowing the collected data to better quantify load using the proposed algorithm (LdIx). AUTORREFERAT